Characterizing Archaeological Rhyolites in the Nenana Valley, Interior Alaska - Angela K. Gore; Kelly Graf; Joshua J. Lynch (Minerals, 2023)
Portable X-ray fluorescence (pXRF) is a useful geochemical technique employed to explore toolstone procurement strategies in the lithic record, commonly utilized in sourcing obsidians. Non-obsidian volcanic toolstones (e.g., dacites, rhyolites, basalts, and andesites) are abundant in interior Alaskan assemblages yet understudied compared to obsidian. Geochemical analyses of these non-obsidian materials offer the potential to gain new insights into ancient toolstone provisioning behaviors. This paper presents a synthesis of geochemical (pXRF) analyses of rhyolite artifacts, systematic regional raw material surveys, and lithic technological analyses collected from nineteen late Pleistocene and Holocene assemblages from the Nenana valley, interior Alaska. Previous research studies on archaeological rhyolites from the region are replicated, new rhyolite artifact groups are identified, and one new rhyolite source is reported and described here. Ultimately, this paper contributes to a growing body of geochemical research seeking to provide a more nuanced look at the complex late Pleistocene and Holocene record of eastern Beringia.